The Impact of Physical Activity and Exercise on Endometriosis Related Symptoms with Particular Emphasis on Pain - Systematic Review - Kuśnierz, Anna; Kusiak, Karolina; Głąbień, Marta; Miłkowski, Paweł; Aleksandrowicz, Daria; Wieczorek, Olga; Jakubczak, Zofia; Kondratowicz, Aneta; Zimniak, Maria Weronika; Śliwiak , Patryk (Quality in Sport, 2024)
Endometriosis is common chronic condition that can cause acute and chronic pain. It affects 5-10 % of women in their reproductive years. It is characterized by the presence of endometrial- like tissue outside the uterus and it is associated with pelvic pain and infertility. Diagnosis of endometriosis requires laparotomy or laparoscopy. Therefore, there is often a delay from initial symptoms to diagnosis and treatment. There is no effective treatment. Current therapeutic methods aim to reduce pain and treat infertility. It include surgery, hormonal treatments and analgesics in case of a pain. Additionally, this methods have their limitations in form of side effects and unsatisfactory therapeutic effect. [1,2] Wherefore physical activity (PA) and exercise have been suggested as alternative treatments.[3] In this study authors perform a systematic review to evaluate the effect of PA and exercise on endometriosis-related symptoms.